Biometry authentication system based on on-line signature verification - Lutskiv, A. (Українські технології, 2006)
New mathematical model, methods of preprocessing, diagnostic attributes, methods of statistical analysis of the dynamic handwritten signature for authentication of the person in computer information systems are proposed. Authentication module as a part of the corporate information system is presented.
Keywords: authentication; on-line signature; biometry